Kerentanan Jenis Tepung terhadap Infestasi Kumbang Tepung Merah (Tribolium castaneum Herbst) (Coleoptera: Tenebrionidae) - Hendrival Hendrival; Latifah Latifah; Dedi Saputra; Orina Orina (Agrikultura, 2016)
ABSTRACT Susceptibility of various flour types to the investation of red flour beetle ( Tribolium castaneum Herbst) (Coleoptera: Tenebrionidae) The research on the level of flour susceptibility against infestation of Tribolium castaneum has been conducted in laboratory under conditions of 28-30oC and relative humidity of 70-75%. Each type of flour was infested by 10 pairs of T. castaneum adult. Variables observation included the population growth, development period, weight losses percentage and susceptibility index. The results showed that degree of flour suitability against population growth namely wheat flour > corn flour > bran > mungbean flour > rice flour > potato flour > purple cultivar sweet potato flour > bread crumbs > glutinous rice flour > tapioca flour = sago flour. The longest median development time of T. castaneum was found in tapioca and sago flours of 86 days while the shortest was in wheat flour of 23.33 days. The highest weight loss percentage occurred on wheat and corn flours. The susceptibility level of flours to T. castaneum with resistant category included tapioca flour, corn flour, glutinous rice flour, purple cultivar sweet potato flour and bread crumbs. Mungbean flour was in moderate gategory while potato flour was in resistant to moderate category. Rice flour and bran were classified in susceptible category while corn and wheat flours were classified as highly susceptible. Keywords: Tribolium castaneum , Flour, Population growth, Development period, Susceptibility ABSTRAK Penelitian tingkat kerentanan jenis tepung terhadap infestasi Tribolium castaneum telah dilakukan di laboratorium pada kondisi suhu 28-30oC dan RH 70-75%. Setiap jenis tepung diinfestasi 10 pasang imago T . c a s t a n e u m . Variabel pengamatan meliputi pertumbuhan populasi, periode perkembangan, persentase susut berat dan indek kerentanan. Hasil penelitian menunjukkan bahwa tingkat kesesuaian jenis tepung terhadap pertumbuhan populasi yaitu tepung gandum > tepung jagung > dedak > tepung kacang hijau > tepung beras > tepung kentang > tepung ubi jalar kultivar ungu > tepung panir > tepung ketan putih > tepung tapioka = tepung sagu. Median waktu perkembangan T. castaneum paling lama dijumpai pada tepung tapioka dan sagu yaitu 86 hari, sedangkan paling singkat pada tepung gandum yaitu 23,33 hari. Susut berat tepung paling banyak terjadi pada tepung gandum dan jagung. Tingkat kerentanan jenis tepung terhadap T. castaneum yaitu katagori resisten meliputi tepung tapioka, tepung sagu, tepung ketan putih, tepung ubi jalar kultivar ungu, dan tepung panir. Katagori moderat yaitu tepung kacang hijau, sedangkan tepung kentang tergolong resisten sampai moderat. Tepung beras dan dedak tergolong katagori rentan, sedangkan tepung jagung dan gandum tergolong katagori sangat rentan. Kata Kunci: Tribolium castaneum , Tepung, Pertumbuhan populasi, Periode perkembangan, Tingkat kerentanan